Zirconia sintered body and its manufacturing method
Patent Information
- Application Number
- JP2022002072
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2016-09-21
- Filing Date
- 2022-01-11
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2037-09-20
AI Technical Summary
【0014】 本発明により、本発明は、歯科材料として広く使用できるジルコニア焼結体、特に奥歯用歯科材料及び前歯用歯科材料のいずれにも適用できるジルコニア焼結体、及びこのようなジルコニア焼結体を簡便に製造できる製造方法を提供することができる。
Smart Images

Figure 0007638234000012 
Figure 0007638234000013 
Figure 0007638234000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a zirconia sintered body having both translucency and high strength, and a method for producing the same. [Background technology]
[0002] Zirconia sintered bodies have high mechanical strength and high aesthetics based on translucency, and are therefore used not only as structural materials and decorative members but also as dental materials (Patent Documents 1 to 4). When used as dental materials, zirconia sintered bodies are required to have high translucency with a total light transmittance of 40% or more and high bending strength of 800 MPa or more (Patent Document 1).
[0003] As a zirconia sintered body that satisfies such requirements, a zirconia sintered body that is manufactured by hot isostatic pressing (hereinafter referred to as "HIP") treatment, has a total light transmittance of 43% or more at a sample thickness of 0.5 mm, a three-point bending strength of 1700 MPa or more, and an yttria content of 2 to 4 mol% has been disclosed (Patent Document 2). However, since the HIP treatment requires a large-scale device, the practical use of the zirconia sintered body of Patent Document 2 is limited.
[0004] Meanwhile, zirconia sintered bodies that do not require HIP treatment and have both high mechanical strength and high translucency, and methods for producing the same, have been investigated.
[0005] Patent Document 1 discloses a method for molding and sintering zirconia powder with a BET specific surface area and crystallinity controlled and an yttria content of about 3 mol%. Patent Document 1 discloses that a zirconia sintered body having a total light transmittance of 41.20% to 44.06% for D65 light at a sample thickness of 0.5 mm and a bending strength of 860 to 891 MPa can be obtained by firing at a maximum temperature of 1450°C and holding for 2 hours. However, the total light transmittance of this zirconia sintered body is only less than 30% at most when converted into a total light transmittance (hereinafter also simply referred to as "total light transmittance") for D65 light at a sample thickness of 1 mm, and the zirconia sintered body of Patent Document 1 has insufficient translucency for use as a dental material.
[0006] Patent Document 3 discloses a zirconia sintered body having mechanical strength and translucency suitable for practical use as a dental material, which is obtained by sintering under normal pressure zirconia powder with an yttria content of 2 to 4 mol%, in which the sintering shrinkage rate and BET specific surface area are controlled until the relative density reaches 70 to 90%, and the zirconia sintered body has a total light transmittance of 35% or more and a three-point bending strength of 1000 MPa or more.
[0007] Patent Document 4 discloses a zirconia sintered body having both high mechanical strength and high translucency and having such high translucency that it can be used as a dental material for anterior teeth, and a method for producing such a zirconia sintered body without using HIP treatment. The zirconia sintered body disclosed in Patent Document 4 has an yttria content of more than 4 mol% and not more than 6.5 mol%, is obtained by normal pressure sintering, has a total light transmittance of 42% or more, and has a three-point bending strength of 550 to 870 MPa.
[0008] The zirconia sintered bodies disclosed in Patent Documents 3 and 4, which can be produced by pressureless sintering, have high mechanical strength and high translucency, and are therefore used as practical dental materials. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2016-108176 A [Patent Document 2] JP 2008-050247 A [Patent Document 3] JP 2010-150063 A [Patent Document 4] JP 2015-143178 A Summary of the Invention [Problem to be solved by the invention]
[0010] The zirconia sintered bodies of Patent Documents 3 and 4 satisfy the mechanical strength and translucency required for dental materials. However, in actual use, materials with higher strength are used as dental materials for back teeth, and materials with higher translucency are used as dental materials for front teeth, and so on, and so on. In addition, Patent Document 4 discloses only one zirconia sintered body with high mechanical strength and translucency, with a total light transmittance of 44% and a three-point bending strength of 870 MPa, but in order to repeatedly produce this zirconia sintered body, it was necessary to control the production conditions very precisely.
[0011] In view of these problems, the present invention aims to provide a zirconia sintered body that can be widely used as a dental material, particularly a zirconia sintered body that can be used as both a dental material for back teeth and a dental material for anterior teeth, and a simple method for producing the same. [Means for solving the problem]
[0012] The present inventors have investigated a zirconia sintered body having both mechanical properties and translucency that satisfy the characteristics required for dental materials, particularly for dental materials for anterior teeth and dental materials for molar teeth, and a method for producing the same, and as a result, have found that such a zirconia sintered body can be easily produced by controlling the state of the raw material powder, thereby completing the present invention.
[0013] That is, the present invention is a method for producing a zirconia sintered body, which is characterized by comprising a molding step of molding a powder composition containing a first zirconia powder having an yttria content of 2 mol% or more and 4 mol% or less, and a second zirconia powder having an yttria content of more than 4 mol% and not more than 6 mol%, and having an yttria content of more than 3 mol% and not more than 5.2 mol% to obtain a molded body, and a sintering step of sintering the molded body to obtain a sintered body. Effect of the Invention
[0014] The present invention can provide a zirconia sintered body that can be widely used as a dental material, particularly a zirconia sintered body that can be applied to both a dental material for back teeth and a dental material for anterior teeth, and a manufacturing method for easily manufacturing such a zirconia sintered body. [Brief description of the drawings]
[0015] [Figure 1] Graph showing yttria concentration distribution in Example 1 [Diagram 2] Graph showing yttria concentration distribution in Comparative Example 2 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the method for producing the zirconia sintered body of the present invention will be described.
[0017] The manufacturing method of the present invention includes a molding step of molding a powder composition (hereinafter simply referred to as "powder composition") containing a first zirconia powder having an yttria content of 2 mol% or more and 4 mol% or less, and a second zirconia powder having an yttria content of more than 4 mol% and not more than 6 mol%, and having an yttria content of more than 3 mol% and not more than 5.2 mol%, to obtain a molded body.
[0018] A powder composition is provided for the molding step. The powder composition has an yttria content of more than 3 mol% and not more than 5.2 mol%. If the yttria content is 3 mol% or less, the resulting zirconia sintered body has a total light transmittance of 42% or less for D65 light at a sample thickness of 1 mm, limiting its application as a dental material. On the other hand, if the yttria content exceeds 5.2 mol%, a zirconia sintered body having a three-point bending strength of 800 MPa or more required for a dental material cannot be obtained even with the manufacturing method of the present invention.
[0019] The yttria content of the powder composition is preferably 3.5 mol % or more and 4.8 mol % or less, more preferably 3.8 mol % or more and 4.6 mol % or less, and even more preferably 3.8 mol % or more and 4.3 mol % or less.
[0020] The powder composition includes a first zirconia powder having an yttria content of 2 mol% or more and 4 mol% or less (hereinafter also referred to as "low yttria powder") and a second zirconia powder having an yttria content of more than 4 mol% and 6 mol% or less (hereinafter also referred to as "high yttria powder"). By sintering such a powder composition, the obtained zirconia sintered body tends to have improved mechanical strength as the average crystal grain size increases, so that a zirconia sintered body having both mechanical strength and translucency that are equal to or greater than the properties required for a dental material can be obtained without controlling the manufacturing conditions in detail.
[0021] The yttria content of the low yttria powder is 2 mol% to 4 mol%, preferably 2 mol% to 3.5 mol%, and more preferably 2.3 mol% to 3.5 mol%, while the yttria content of the high yttria powder is more than 4 mol% to 6 mol%, preferably 4 mol% to 5.7 mol%, and more preferably 4.5 mol% to 5.7 mol%.
[0022] In the present invention, the powder composition preferably contains zirconia powder having an yttria content of 2.3 mol % or more and 3.5 mol % or less as the low yttria powder, and zirconia powder having an yttria content of 5.2 mol % or more and 5.7 mol % or less as the high yttria powder.
[0023] The content ratio of the low yttria powder and the high yttria powder in the powder composition may be any ratio that allows the powder composition to have the desired yttria content. The content ratio of the low yttria powder and the high yttria powder in the powder composition varies depending on the yttria content of each powder, but the weight ratio of the low yttria powder to the high yttria powder can be low yttria powder: high yttria powder = 1 weight %: 99 weight % to 99 weight %: 1 weight %. More preferred weight ratios include low yttria powder: high yttria powder = 20 weight %: 80 weight % to 80 weight %: 20 weight %, and even 35 weight %: 65 weight % to 65 weight %: 35 weight %.
[0024] The low-yttria powder and the high-yttria powder can be produced by a production method including a hydrolysis step of obtaining a hydrated zirconia sol by hydrolysis of an aqueous zirconium salt solution, a drying step of mixing the obtained hydrated zirconia sol with an yttrium compound and then drying to obtain a dry powder, and a calcination step of calcining the dried powder to obtain a calcined powder. A preferred production method for the low-yttria powder and the high-yttria powder includes, for example, a production method in which at least one of yttrium oxide or yttrium chloride is mixed with a hydrated zirconia sol obtained by hydrolyzing at least one of the group consisting of zirconium oxychloride salts, zirconyl nitrate salts, zirconium chloride salts, and zirconium sulfate salts, and then drying the mixture in air at 80°C to 200°C, and then calcining the mixture in air at 1050°C to 1250°C.
[0025] The powder composition is alumina (Al 2 O 3The alumina content of the powder composition can be, in terms of the weight ratio of alumina to the weight of the powder composition, 0% by weight or more and 0.1% by weight or less, further 0% by weight or more and less than 0.1% by weight, and further 0% by weight or more and 0.075% by weight or less, and when the powder composition contains alumina, the alumina content can be, in terms of the weight ratio of alumina to the weight of the powder composition, more than 0% by weight or more and 0.1% by weight or less, further more than 0% by weight or more and 0.1% by weight or less, further more than 0% by weight or more and 0.075% by weight or less, and further more 0.01% by weight or more and 0.075% by weight or less.
[0026] The crystallite diameter of the powder composition is 200 Å to 400 Å, and further 300 Å to 400 Å. The crystallite diameter of the powder composition can be calculated from the XRD peaks (hereinafter also referred to as "main XRD peaks") of the tetragonal (111) plane and the cubic (111) plane in powder X-ray diffraction (hereinafter referred to as "XRD") measurement by the following formula. Crystallite size = κλ / βcosθ
[0027] In the above formula, κ is the Scherrer constant (κ=1), λ is the wavelength of the measured X-rays (when CuKα rays are used as the radiation source, λ=1.541862 Å), β is the half-width (°) of the main XRD peak, and θ is the Bragg angle of the main XRD peak.
[0028] The main XRD peak is an XRD peak that appears at 2θ=30.1 to 30.2° in XRD using CuKα radiation as a radiation source. This peak is an XRD peak where the (111) plane of the tetragonal crystal and the (111) plane of the cubic crystal overlap. When calculating the crystallite size, the main XRD peak is processed without separating the tetragonal and cubic crystal peaks. The Bragg angle (θ) of the main XRD peak after processing and the half-width (β) of the main XRD peak corrected for mechanical broadening width are obtained.
[0029] The powder composition preferably has a ratio of tetragonal and cubic crystals (hereinafter also referred to as "T+C phase ratio") calculated by the following formula of 60% or more, more preferably 65% or more.
[0030] T+C phase ratio (%) = 100-fm(%) In the above formula, fm is the monoclinic phase ratio determined from the XRD pattern.
[0031] In order to make the physical properties of the powder composition uniform, it is preferable that the powder composition, the low-yttria powder and the high-yttria powder have approximately the same BET specific surface area and average particle size.
[0032] The preferred BET specific surface area is 5 m 2 / g or more 17m 2 / g or even less than 5m 2 / g or more 15m 2 The preferred average particle size is 0.30 μm or more and 0.60 μm or less, further 0.35 μm or more and 0.55 μm or less, and further 0.40 μm or more and 0.50 μm or less.
[0033] The powder composition may be produced by any method as long as it contains a low yttria powder and a high yttria powder and has a desired composition. The powder composition may be conveniently obtained by mixing a low yttria powder and a high yttria powder. As long as the two are homogeneous, any mixing method may be used, including at least one of dry mixing and wet mixing, and further wet mixing. A preferred mixing method is mixing in an aqueous solvent. In order to achieve homogeneous mixing, it is preferable to use ungranulated powders such as calcined powders for the low yttria powder and the high yttria powder.
[0034] When the powder composition contains alumina, the low yttria powder and the high yttria powder may be mixed together and then alumina is added to form the powder composition. However, it is preferable to mix at least one of the low yttria powder or the high yttria powder with alumina, and then mix the low yttria powder and the high yttria powder to form the powder composition.
[0035] The powder composition to be subjected to the molding step is preferably a granulated powder. Granulated powder compositions have high fluidity and are therefore more likely to be densified during sintering. Granulated powders have an average particle size of 30 μm or more and 80 μm or less, and a bulk density of 1.10 g / cm. 3 More than 1.40g / cm 3 The following are some of the reasons:
[0036] The granulated powder is obtained by mixing the powder composition with an organic binder and spray drying the mixture. The content of the organic binder in the granulated powder is, for example, 1% by weight or more and 5% by weight or less based on the weight of the powder composition.
[0037] In the molding step, any molding method can be used as long as a molded body having a desired shape can be obtained. Examples of the molding method include at least one method selected from the group consisting of press molding, cold isostatic pressing, sheet molding, and injection molding.
[0038] The shape of the molded body is arbitrary, and may be at least one of the shape consisting of a sphere, an approximately sphere, an ellipse, a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, and an approximately polyhedron.
[0039] The manufacturing method of the present invention may include a calcination step in which the compact obtained in the molding step is calcined to obtain a calcined body. The calcination step is a step between the molding step and the sintering step. The calcination step produces a zirconia calcined body having an yttria content of more than 3 mol% and not more than 5.2 mol%, furthermore 3.5 mol% to 4.8 mol%, furthermore 3.8 mol% to 4.6 mol%, and furthermore 3.8 mol% to 4.3 mol%. The calcined body is a compact in the early stage of sintering, and has a structure including necking between powders. In the calcination step, the calcined body can be processed into any shape.
[0040] The calcination is preferably carried out at a calcination temperature of 600°C or higher and 1400°C or lower, more preferably 600°C or higher and 1200°C or lower, and even more preferably 800°C or higher and 1100°C or lower.
[0041] The holding time at the calcination temperature can be, for example, from 1 hour to 5 hours, further from 1 hour to 3 hours, and further from 1 hour to 2 hours.
[0042] The calcination atmosphere may be any atmosphere other than a reducing atmosphere, and is preferably at least one of an oxygen atmosphere and an air atmosphere, and it is convenient to use an air atmosphere.
[0043] In the sintering step, the molded body obtained in the molding step is sintered to obtain a sintered body, which results in a zirconia sintered body having an yttria content of more than 3 mol% and not more than 5.2 mol%, furthermore, 3.5 mol% to 4.8 mol%, furthermore, 3.8 mol% to 4.6 mol%, and furthermore, 3.8 mol% to 4.3 mol%.
[0044] When the production method of the present invention includes a calcination step, the calcined body may be sintered in the sintering step instead of the molded body.
[0045] The sintering temperature in the sintering step is preferably 1400° C. to 1600° C., more preferably 1420° C. to 1580° C., even more preferably 1440° C. to 1560° C., and even more preferably 1480° C. to 1560° C. Other sintering temperatures include 1450° C. to 1650° C., 1500° C. to 1650° C., 1500° C. to 1650° C., and 1550° C. to 1650° C.
[0046] The heating rate in the sintering step can be 150° C. / hour to 800° C. / hour, further 150° C. / hour to 700° C. / hour, and further 200° C. / hour to 600° C. / hour. This makes it possible to suppress the progress of sintering during the heating process and sinter the molded body at the sintering temperature.
[0047] The holding time at the sintering temperature (hereinafter also simply referred to as "holding time") varies depending on the sintering temperature. The holding time can be, for example, from 1 hour to 5 hours, from 1 hour to 3 hours, or from 1 hour to 2 hours.
[0048] The sintering atmosphere may be any atmosphere other than a reducing atmosphere, and is preferably at least one of an oxygen atmosphere and an air atmosphere, and it is convenient to use an air atmosphere.
[0049] A particularly preferred sintering step is one in which sintering is performed under atmospheric pressure at a heating rate of 700° C. / hour or less at a sintering temperature of 1440° C. or more and 1560° C. or less.
[0050] In the sintering step, any sintering method can be applied. As the sintering method, at least one of the group consisting of atmospheric sintering, HIP treatment, PSP, and vacuum sintering can be mentioned. In general, as a means for improving the translucency, after obtaining a sintered body by atmospheric sintering, a special sintering method such as HIP or other pressure sintering or SPS can be used. However, the special sintering method not only complicates the manufacturing process but also causes an increase in manufacturing costs. Therefore, it is preferable that the sintering step in the present invention is atmospheric sintering, and more preferably, only atmospheric sintering. Normal pressure sintering is a method in which a molded body is sintered by simply heating it without applying an external force during sintering. As a specific normal pressure sintering, sintering under atmospheric pressure can be mentioned.
[0051] One of the features of the manufacturing method of the present invention is that the decrease in mechanical strength associated with the increase in the average crystal grain size of the obtained zirconia sintered body tends to be significantly smaller as the sintering temperature increases, and further, the mechanical strength may increase with the increase in the average crystal grain size. This makes it easier to obtain a zirconia sintered body having a higher total light transmittance while maintaining high mechanical strength. Therefore, it is possible to easily manufacture a zirconia sintered body that has both mechanical properties and translucency that satisfy the properties required for both dental materials for anterior teeth and dental materials for molar teeth without detailed control of manufacturing conditions.
[0052] In another aspect, the present invention can also be provided as a method for producing a zirconia calcined body, comprising: a molding step of molding a powder composition containing a first zirconia powder having an yttria content of 2 mol% or more and 4 mol% or less, and a second zirconia powder having an yttria content of more than 4 mol% and not more than 6 mol%, and having an yttria content of more than 3 mol% and not more than 5.2 mol% to obtain a molded body; and a calcination step of calcining the molded body to obtain a calcined body.
[0053] The zirconia sintered body obtained by the manufacturing method of the present invention has a wider yttria concentration distribution than conventional sintered bodies. That is, the manufacturing method of the present invention can provide a zirconia sintered body having an yttria content of more than 3 mol% and not more than 5.2 mol%, and further having a maximum frequency of 7.5% or less in the yttrium concentration distribution in quantitative elemental analysis of energy dispersive X-ray spectroscopy.
[0054] The zirconia sintered body obtained by the production method of the present invention preferably has an yttria content of 3.5 mol % or more and 4.8 mol % or less, more preferably 3.8 mol % or more and 4.6 mol % or less, and even more preferably 3.8 mol % or more and 4.3 mol % or less.
[0055] In the present invention, the yttria content of the zirconia sintered body is the average composition of the sintered body determined by composition analysis, and can be measured by ICP measurement.
[0056] The zirconia sintered body obtained by the manufacturing method of the present invention has a maximum frequency of yttrium concentration distribution in quantitative elemental analysis of energy dispersive X-ray spectroscopy (hereinafter, also simply referred to as "frequency") of 7.5% or less, preferably 7.0% or less.
[0057] The fact that the maximum frequency (hereinafter also referred to as "maximum frequency") is 7.5% or less means that the zirconia sintered body obtained by the manufacturing method of the present invention has many regions of different yttria concentrations in the sintered body. It is considered that one of the reasons that the yttrium content is within the above range and that the sintered body has such an yttria distribution contributes to improving the mechanical properties of the sintered body. The maximum frequency can be 3.0% or more, and further 5.0% or more.
[0058] Quantitative analysis of elements in EDS spectrum can be performed by obtaining an EDS spectrum for a scanning electron microscope (hereinafter also referred to as "SEM") observation image of the sintered body, and quantifying the intensities of characteristic X-rays of zirconium (Zr) and yttrium (Y) in the obtained EDS spectrum. Quantitative analysis of EDS spectrum can be performed by measuring 40,000 or more randomly selected points in the SEM observation image. The yttrium concentration is preferably determined as the ratio of the intensity of yttrium to the intensity of zirconium (hereinafter also referred to as "Y / Zr ratio"). The yttrium concentration distribution is preferably an yttrium concentration distribution shown by dividing a certain yttrium concentration into concentration ranges, and can be an yttrium concentration distribution shown by dividing the Y / Zr ratio into concentration ranges of 0.5% each. The frequency is the ratio (%) of the number of measurement points corresponding to each yttrium concentration to the total number of measurement points in the quantitative determination of the EDS spectrum. Since the sintered body obtained by the manufacturing method of the present invention has a homogeneous composition on the surface and inside, the yttrium concentration distribution of the entire sintered body can be measured by EDS observation of the surface.
[0059] The crystal phase of the zirconia sintered body obtained by the manufacturing method of the present invention is composed of tetragonal crystals. The tetragonal crystals are composed of T phase and T * It is preferable that the crystal phase contains a T phase. * The ratio of the phases (hereinafter referred to as "T * The ratio of T to T is 62% or more and less than 100%, and preferably 65% or more and less than 100%. * The / T ratio is more preferably 76% or more and less than 100%, and even more preferably 76% or more and 90% or less.
[0060] The zirconia sintered body obtained by the manufacturing method of the present invention is made of alumina (Al 2 O 3 The alumina content of the zirconia sintered body obtained by the manufacturing method of the present invention can be 0% by weight or more and 0.1% by weight or less, further 0% by weight or more and less than 0.1% by weight, and further 0% by weight or more and 0.075% by weight or less, as a weight ratio of alumina to the weight of the zirconia sintered body obtained by the manufacturing method of the present invention, and when the zirconia sintered body obtained by the manufacturing method of the present invention contains alumina, the alumina content can be more than 0% by weight and 0.1% by weight or less, further more than 0% by weight and less than 0.1% by weight, further more than 0% by weight and 0.075% by weight or less, and further more than 0.01% by weight and 0.075% by weight or less, as a weight ratio of alumina to the weight of the zirconia sintered body obtained by the manufacturing method of the present invention.
[0061] The mechanical strength and translucency of zirconia sintered bodies are affected by the average crystal grain size, and there is a trade-off between the two. In other words, as the average crystal grain size decreases, the mechanical strength increases, but the translucency decreases. Conversely, as the average crystal grain size increases, the mechanical strength decreases, but the translucency increases. In order to achieve both the mechanical strength and translucency required for dental materials, the yttria content is increased by exceeding 3 mol%, thereby increasing the translucency, and the mechanical strength is increased by setting the average crystal grain size to approximately 0.41 μm.
[0062] In contrast, in the manufacturing method of the present invention, even if the average crystal grain size is more than 0.41 μm, further 0.42 μm or more, or even 0.45 μm or more, a zirconia sintered body having mechanical strength equal to or greater than the mechanical strength required for dental materials can be manufactured. The average crystal grain size of the zirconia sintered body obtained by the manufacturing method of the present invention can be 1.5 μm or less, or even 1.0 μm or less. The average crystal grain size is more preferably 0.55 μm or more and 1.5 μm or less, or even 0.6 μm or more and 1.0 μm or less.
[0063] Preferably, the manufacturing method of the present invention provides a zirconia sintered body having an yttria content of more than 3 mol% and not more than 5.2 mol% and an average crystal grain size of 0.42 μm or more. The zirconia sintered body is a so-called translucent zirconia sintered body having higher mechanical strength and translucency than those required for dental materials.
[0064] The zirconia sintered body obtained by the manufacturing method of the present invention is obtained by normal pressure sintering, and has high mechanical strength even though it has such a large average crystal grain size. The mechanical strength of the zirconia sintered body obtained by the manufacturing method of the present invention is 810 MPa or more, and even more than 870 MPa, and preferably 900 MPa or more, as a three-point bending strength obtained by a measurement method according to JIS R 1601. In particular, the zirconia sintered body obtained by the manufacturing method of the present invention can have a high three-point bending strength of 900 MPa or more and 1300 MPa or less, and even 900 MPa or more and 1200 MPa or less, even if the yttria content is 3.8 mol% or more and 4.2 mol% or less, and even 3.8 mol% or more and 4.15 mol% or less.
[0065] The zirconia sintered body obtained by the manufacturing method of the present invention has the above mechanical strength, and has a total light transmittance of 43% or more, further exceeding 44%, and further exceeding 44.5%. When the yttria content is more than 3 mol% and not more than 5.2 mol%, the total light transmittance is 49% or less. In the present invention, the total light transmittance can be measured by a method conforming to JIS K 7361 using a D65 light source and a sintered body having a sample thickness of 1 mm.
[0066] Such a zirconia sintered body can be used as a zirconia sintered body that does not impair the translucency of the zirconia sintered body for conventional dental materials, and has a higher translucency than that of the zirconia sintered body for conventional dental materials, and also has the mechanical strength required for a dental material. Thus, the zirconia sintered body obtained by the production method of the present invention can be used as a dental material, and can be used as a dental material for both molars and anterior teeth. EXAMPLES
[0067] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.
[0068] The method for measuring the characteristics of the sintered body and powder of the present invention will be described below.
[0069] (Total light transmittance) The total light transmittance was measured by a method in accordance with JIS K 7361 using a turbidity meter (device name: NDH2000, manufactured by Nippon Denshoku Industries Co., Ltd.) and a D65 light source.
[0070] The measurement sample used was a double-sided polished disk-shaped sintered body having a thickness of 1 mm.
[0071] (3-point bending strength) The bending test was performed using a three-point bending test based on JIS R 1601 "Testing method for bending strength of fine ceramics". The measurement was performed 10 times, and the average value was taken as the three-point bending strength. The measurement was performed using a columnar sintered sample with a width of 4 mm and a thickness of 3 mm, with a support distance of 30 mm.
[0072] (Sintered body density) The actual density of the sintered body was measured using a method based on JIS R 1634 (Method of measurement of sintered density and open porosity of fine ceramics). The relative density was calculated from the ratio of the actual density to the theoretical density.
[0073] Theoretical density (ρ 0) was calculated using the following formula (1). ρ 0 =100 / [(A / ρ A )+(100-A) / ρ X ]
[0074] In the above formula, ρ 0 is the theoretical density (g / cm 3 ), A is Al 2 O 3 Content (wt%), ρ A Al 2 O 3 Theoretical density (3.99 g / cm 3 ), and ρ X is the theoretical density (g / cm) of zirconia sintered body containing Xmol% yttria 3 ).
[0075] In the above formula, ρ X The theoretical density ρ X The value calculated from the formula described in J. Am. Ceram. Soc., 69[4]325-32 (1986) (hereinafter also referred to as the "reference material") may be used.
[0076] (Average grain size) The average crystal grain size of the sintered samples was determined by the planimetric method from SEM photographs taken with a field emission scanning electron microscope (FESEM). That is, the mirror-polished sintered samples were thermally etched and observed with a field emission scanning electron microscope (instrument name: JSM-T220, manufactured by JEOL Ltd.). The average crystal grain size was calculated from the obtained SEM photographs by the planimetric method.
[0077] (Yttria concentration distribution) The maximum frequency was measured using FE-SEM / EDS (apparatus name: JSM-7600F, manufactured by JEOL Ltd.) as follows. The surface of the sintered body was observed with an SEM at 24,000 times magnification to obtain an SEM observation diagram. The EDS spectrum of 40,000 points of the obtained SEM observation diagram was measured, and the intensities of the characteristic X-rays of zirconium and yttrium were quantitatively analyzed to determine the yttrium concentration (Y / Zr ratio) relative to the zirconium concentration. The yttrium concentration distribution was divided into ranges of 0.5% in the range where the Y / Zr ratio exceeded 0.25%, and the frequency in each yttrium concentration range was plotted.
[0078] Prior to the measurement, the sintered samples were pretreated by Ag sputter coating.
[0079] (crystalline phase) XRD measurements of the sintered samples were performed using a general X-ray diffraction device (device name: X'Pert PRO MPD, manufactured by Spectris). The XRD measurement conditions are shown below. The obtained XRD patterns were subjected to Rietveld analysis using RIETAN-2000 to identify the crystal phase of the sintered samples. Radiation source: CuKα radiation (λ=0.1541862nm) Measurement mode: Continuous scan Scan speed: 1° / min Step width: 0.02° Divergence slit: 0.5deg Scattering slit: 0.5deg Receiving slit: 0.3mm Measurement range: 2θ=10°~140°
[0080] (average powder particle size) The average particle size of the zirconia powder was measured using a Microtrac particle size distribution analyzer (device name: 9320-HRA, manufactured by Honeywell Corporation).
[0081] As a pretreatment, the sample powder was suspended in distilled water to form a slurry, which was then dispersed for 3 minutes using an ultrasonic homogenizer (device name: US-150T, manufactured by Nippon Seiki Seisakusho).
[0082] Here, the average particle size of the zirconia powder is the median diameter, which is the center value of the cumulative curve of the particle size distribution expressed on a volume basis, i.e., the diameter of a sphere having the same volume as a particle having a particle size corresponding to 50% of the cumulative curve. The average particle size is a value measured by a particle size distribution measuring device using a laser diffraction method.
[0083] (Crystallite size of powder composition) The crystallite size of the powder composition was calculated from the main XRD peak using the following formula. Crystallite size = κλ / βcosθ
[0084] In the above formula, κ is the Scherrer constant (κ=1), λ is the wavelength of the measured X-rays (when CuKα rays are used as the radiation source, λ=1.541862 Å), β is the half-width (°) of the main XRD peak, and θ is the Bragg angle of the main XRD peak.
[0085] (Crystalline Phase of Powder Composition) The T+C phase ratio was calculated from the XRD pattern of the crystalline phase of the powder composition by the following formula.
[0086] T+C phase ratio (%) = 100-fm(%) In the above formula, fm is the monoclinic fraction.
[0087] (Average particle size of granulated powder) The average particle size of the granulated powder was determined by a sieve analysis method.
[0088] Example 1 (Low yttria powder) A hydrated zirconia sol was obtained by hydrolysis of an aqueous solution of zirconium oxychloride. Yttria was added to the hydrated zirconia sol so that the yttria concentration was 2.5 mol%, and then the sol was dried and calcined to obtain calcined zirconia powder containing yttria. The calcination conditions were 1160°C for 2 hours in air. The calcined powder obtained was washed with distilled water and then dried to obtain zirconia powder containing 2.5 mol% yttria.
[0089] Al per weight of the powder 2 O 3 α-alumina with an average particle size of 0.3 μm was mixed with zirconia powder containing 2.5 mol % yttria so that the content was 0.05 wt %, and then distilled water was added to make a slurry, which was then pulverized and mixed to obtain a slurry containing the low yttria powder of this example. The pulverization and mixing was performed in a water solvent using a ball mill using zirconia balls with a diameter of 2 mm as the pulverization medium, and the mixing time was 24 hours.
[0090] The obtained low yttria powder had an yttria content of 2.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 11.2 m 2 / g and the average particle size was 0.42 μm.
[0091] (High yttria powder) A zirconia powder containing 5.5 mol % yttria and 0.05 wt % alumina was obtained in a similar manner, except that yttria was added to the hydrated zirconia sol so that the yttria concentration was 5.5 mol %, and this was used as the high yttria powder of this example. The resulting yttria-rich powder had an yttria content of 5.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 10.1 m. 2 / g and the average particle size was 0.40 μm.
[0092] (Powder composition) After pulverization and mixing, the low yttria powder slurry and the high yttria powder slurry were mixed in a ratio of 50% by weight:50% by weight and thoroughly stirred to obtain a slurry containing the powder composition of this example. 3% by weight of an organic binder was added to the slurry containing the powder composition, which was then spray-dried to obtain a granulated powder. The granulated powder had an average particle size of 44 μm and a loose bulk density of 1.28 g / cm. 3 The evaluation results of the powder composition of this example are shown in Table 1.
[0093] [Table 1]
[0094] (Sintered body) The obtained powder granules were molded by a uniaxial press at 19.6 MPa, and then molded by a cold isostatic press (hereinafter also referred to as "CIP") process at 196 MPa to obtain a molded body. The obtained molded body was sintered under atmospheric pressure at a sintering temperature of 1450°C, a heating rate of 600°C / hr, and a holding time of 2 hours in an air atmosphere to obtain a zirconia sintered body of this example with an yttria content of 4.0 mol%.
[0095] The crystal phase of the zirconia sintered body of this example is composed of only tetragonal crystals, and the tetragonal crystals are composed of T phase and T * Including phase, T * The / T ratio was 69.5%.
[0096] The evaluation results of the zirconia sintered body of this example are shown in Table 2.
[0097] Example 2 A zirconia sintered body of this example having an yttria content of 4.0 mol% was obtained by the same method as in Example 1, except that the powder composition obtained in Example 1 was used and the sintering temperature was set to 1500° C. The evaluation results of the zirconia sintered body of this example are shown in Table 2.
[0098] Example 3 A zirconia sintered body of this example having an yttria content of 4.0 mol % was obtained in the same manner as in Example 1, except that the powder composition obtained in Example 1 was used and the sintering temperature was 1550°C.
[0099] The crystal phase of the zirconia sintered body of this example is composed of only tetragonal crystals, and the tetragonal crystals are composed of T phase and T * Including phase, T * The / T ratio was 81.8%. The maximum frequency of the zirconia sintered body of this example was 6.9%. The yttria concentration distribution is shown in Figure 1.
[0100] The evaluation results of the zirconia sintered body of this example are shown in Table 2.
[0101] Example 4 A molded body was obtained in the same manner as in Example 1 using the powder composition obtained in Example 1, and this was calcined at a calcination temperature of 1000° C. to obtain a calcined body.
[0102] The calcined body was sintered in the same manner as in Example 1, except that the calcined body was used instead of the molded body and the sintering temperature was set to 1600°C, to obtain a zirconia sintered body of this example having an yttria content of 4.0 mol%.
[0103] The crystal phase of the zirconia sintered body of this example is composed of only tetragonal crystals, and the tetragonal crystals are composed of T phase and T * The maximum frequency of the zirconia sintered body of this example was 6.9%.
[0104] The evaluation results of the zirconia sintered body of this example are shown in Table 2.
[0105] [Table 2]
[0106] From the above table, it can be confirmed that in the manufacturing method of the present invention, as the sintering temperature increases, the obtained sintered body has a light transmittance of 44% or more, while having a strength of 900 MPa or more, and even 1000 MPa or more.
[0107] Example 5 (Low yttria powder) A low yttria powder was obtained in the same manner as in Example 1. The obtained low yttria powder had an yttria content of 2.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 11.2 m 2 / g and the average particle size was 0.41 μm. (High yttria powder) A high yttria powder was obtained in the same manner as in Example 1. The obtained high yttria powder had an yttria content of 5.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 10.1 m 2 / g and the average particle size was 0.42 μm. (Powder composition) After pulverization and mixing, the low yttria powder slurry and the high yttria powder slurry were mixed in a ratio of 55% by weight:45% by weight and thoroughly stirred to obtain a slurry containing the powder composition of this example. 3% by weight of an organic binder was added to the slurry containing the powder composition, which was then spray-dried to obtain a granulated powder. The granulated powder had an average particle size of 46 μm and a loose bulk density of 1.29 g / cm. 3 The evaluation results of the powder composition of this example are shown in Table 3.
[0108] [Table 3]
[0109] (Sintered body) A green body and a sintered body were obtained in the same manner as in Example 1. The evaluation results of the zirconia sintered body of this example, which had an yttria content of 3.85 mol%, are shown in Table 4.
[0110] Example 6 A zirconia sintered body of this example having an yttria content of 3.85 mol% was obtained by the same method as in Example 4, except that the powder composition obtained in Example 5 was used and the sintering temperature was 1500° C. The evaluation results of the zirconia sintered body of this example are shown in Table 4.
[0111] Example 7 A zirconia sintered body of this example having an yttria content of 3.85 mol% was obtained by the same method as in Example 4, except that the powder composition obtained in Example 5 was used and the sintering temperature was 1550° C. The evaluation results of the zirconia sintered body of this example are shown in Table 4.
[0112] [Table 4]
[0113] Example 8 (Low yttria powder) A low-yttria powder was obtained in the same manner as in Example 1, except that yttria was added to the hydrated zirconia sol so that the yttria concentration was 3.0 mol%, the calcination temperature was 1100°C, and the mixing time in the ball mill was 16 hours. The obtained low-yttria powder had an yttria content of 3.0 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 13.1 m. 2 / g and the average particle size was 0.40 μm. (High yttria powder) A high yttria powder was obtained in the same manner as in Example 1. The obtained high yttria powder had an yttria content of 5.5 mol %, an alumina content of 0.05 wt %, and a BET specific surface area of 10.1 m 2 / g and the average particle size was 0.41 μm. (Powder composition) The slurry of the low yttria powder and the slurry of the high yttria powder after pulverization and mixing were mixed in a ratio of 60% by weight:40% by weight and thoroughly stirred to obtain a slurry containing the powder composition of this example. After adding 3% by weight of an organic binder to the slurry containing the powder composition, this was spray-dried to obtain a granulated powder. The granulated powder had an average particle size of 43 μm and a loose bulk density of 1.27 g / cm. 3 The evaluation results of the powder composition of this example are shown in Table 5.
[0114] [Table 5]
[0115] (Sintered body) A green body and a sintered body having an yttria content of 4.0 mol % were obtained in the same manner as in Example 1. The evaluation results of the zirconia sintered body of this example are shown in Table 6.
[0116] Example 9 A zirconia sintered body of this example having an yttria content of 4.0 mol% was obtained by the same method as in Example 7, except that the powder composition obtained in Example 8 was used and the sintering temperature was set to 1500° C. The evaluation results of the zirconia sintered body of this example are shown in Table 6.
[0117] Example 10 A zirconia sintered body of this example having an yttria content of 4.0 mol% was obtained in the same manner as in Example 8, except that the powder composition obtained in Example 8 was used and the sintering temperature was set to 1550° C. The evaluation results of the zirconia sintered body of this example are shown in Table 6.
[0118] [Table 6]
[0119] Example 11 (Low yttria powder) A low yttria powder was obtained in the same manner as in Example 1. The obtained low yttria powder had an yttria content of 2.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 11.2 m 2 / g and the average particle size was 0.39 μm. (High yttria powder) A high yttria powder was obtained in the same manner as in Example 1. The obtained high yttria powder had an yttria content of 5.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 10.1 m 2 / g and the average particle size was 0.40 μm. (Powder composition) The slurry of the low yttria powder and the slurry of the high yttria powder after pulverization and mixing were mixed in a ratio of 45% by weight:55% by weight and thoroughly stirred to obtain a slurry containing the powder composition of this example. After adding 3% by weight of an organic binder to the slurry containing the powder composition, this was spray-dried to obtain a granulated powder. The granulated powder had an average particle size of 42 μm and a loose bulk density of 1.27 g / cm. 3 The evaluation results of the powder composition of this example are shown in Table 7.
[0120] [Table 7]
[0121] (Sintered body) A green body and a sintered body having an yttria content of 4.15 mol % were obtained in the same manner as in Example 1. The evaluation results of the zirconia sintered body of this example are shown in Table 8.
[0122] Example 12 A zirconia sintered body of this example having an yttria content of 4.15 mol% was obtained by the same method as in Example 11, except that the powder composition obtained in Example 11 was used and the sintering temperature was 1500° C. The evaluation results of the zirconia sintered body of this example are shown in Table 8.
[0123] Example 13 A zirconia sintered body of this example having an yttria content of 4.15 mol% was obtained by the same method as in Example 11, except that the powder composition obtained in Example 11 was used and the sintering temperature was 1550° C. The evaluation results of the zirconia sintered body of this example are shown in Table 8.
[0124] [Table 8]
[0125] The above table shows that even in the case of a sintered body having an yttria content exceeding 4.0 mol%, the strength improves to 870 MPa or more, further to 900 MPa or more, and further to 1000 MPa or more as the sintering temperature increases.
[0126] Example 14 (Low yttria powder) A low yttria powder was obtained in the same manner as in Example 8. The obtained low yttria powder had an yttria content of 3.0 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 13.0 m 2 / g and the average particle size was 0.40 μm. (High yttria powder) A high yttria powder was obtained in the same manner as in Example 1. The obtained high yttria powder had an yttria content of 5.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 10.0 m 2 / g and the average particle size was 0.41 μm. (Powder composition) After pulverization and mixing, the low yttria powder slurry and the high yttria powder slurry were mixed in a ratio of 40% by weight:60% by weight and thoroughly stirred to obtain a slurry containing the powder composition of this example. 3% by weight of an organic binder was added to the slurry containing the powder composition, which was then spray-dried to obtain a granulated powder. The granulated powder had an average particle size of 45 μm and a loose bulk density of 1.29 g / cm. 3 The evaluation results of the powder composition of this example are shown in Table 9.
[0127] [Table 9]
[0128] (Sintered body) A green body and a sintered body having an yttria content of 4.5 mol % were obtained in the same manner as in Example 1. The evaluation results of the zirconia sintered body of this example are shown in Table 10.
[0129] Example 15 A zirconia sintered body of this example having an yttria content of 4.5 mol% was obtained in the same manner as in Example 14, except that the powder composition obtained in Example 14 was used and the sintering temperature was 1500° C. The evaluation results of the zirconia sintered body of this example are shown in Table 10.
[0130] Example 16 A zirconia sintered body of this example having an yttria content of 4.5 mol% was obtained in the same manner as in Example 14, except that the powder composition obtained in Example 11 was used and the sintering temperature was set to 1550° C. The evaluation results of the zirconia sintered body of this example are shown in Table 10.
[0131] [Table 10]
[0132] As can be seen from the above table, the sintered body with an yttria content of 4.5 mol% has a lower strength than the sintered body with an yttria content of 4.0 mol%; however, both exceed 800 MPa, demonstrating practical strength for use as a dental material.
[0133] Comparative Example 1 (Low yttria powder) A low yttria powder was obtained in the same manner as in Example 8. The obtained low yttria powder had an yttria content of 3.0 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 12.9 m 2 / g and the average particle size was 0.42 μm. (High yttria powder) A high yttria powder was obtained in the same manner as in Example 1. The obtained high yttria powder had an yttria content of 5.5 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 9.9 m 2 / g and the average particle size was 0.43 μm. (Powder composition) After pulverization and mixing, the low yttria powder slurry and the high yttria powder slurry were mixed in a ratio of 10% by weight:90% by weight and thoroughly stirred to obtain a slurry containing the powder composition of this example. 3% by weight of an organic binder was added to the slurry containing the powder composition, which was then spray-dried to obtain a granulated powder. The granulated powder had an average particle size of 43 μm and a loose bulk density of 1.28 g / cm. 3 The evaluation results of the powder composition of this comparative example are shown in Table 11.
[0134] [Table 11]
[0135] (Sintered body) A green body and a sintered body with an yttria content of 5.25 mol% were obtained in the same manner as in Example 1. The three-point bending strength of the sintered body of this comparative example was 613 MPa, which does not have the bending strength required for dental applications, and it was confirmed that a zirconia sintered body with an yttria content exceeding 5.2 mol% has a low mechanical strength.
[0136] Comparative Example 2 A hydrated zirconia sol was obtained by hydrolyzing an aqueous solution of zirconium oxychloride. A zirconia powder was obtained in the same manner as in the low yttria powder of Example 1, except that yttria was added to the hydrated zirconia sol so that the yttria concentration was 4.0 mol%, and this was used as the zirconia powder of this comparative example.
[0137] The obtained low yttria powder had an yttria content of 4.0 mol%, an alumina content of 0.05 wt%, and a BET specific surface area of 11.2 m 2 / g and the average particle size was 0.41 μm.
[0138] A green body and a sintered body having an yttria content of 4.0 mol % were obtained in the same manner as in Example 1, except that the zirconia powder of this example was used and the sintering temperature was set to 1550°C.
[0139] The zirconia sintered body of this comparative example has a crystal phase consisting of only tetragonal crystals, and the tetragonal crystals are a T phase and a T * Including phase, T * The / T ratio was 75.4%. The maximum frequency of the zirconia sintered body of this comparative example was 8.0%. The yttria concentration distribution is shown in Figure 2.
[0140] The sintered body of this comparative example had a total light transmittance of 45.3% and a three-point bending strength of 870 MPa. This was a lower strength than the sintered body of Example 11, which was obtained at the same sintering temperature and had an yttria content of 4.1 mol%. Furthermore, the minimum bending strength of this comparative example was 703 MPa, and there was a large variation. This confirmed that the manufacturing method of the present invention can obtain sintered bodies having higher strength than conventional ones. In addition, the sintered body of this comparative example had a T * It was shown that the / T ratio was high and yttria was distributed more uniformly than in the sintered bodies of the examples. [Industrial Applicability]
[0141] The method for producing a zirconia sintered body of the present invention is a method for producing a zirconia sintered body having both high translucency and high mechanical strength with good reproducibility, and can be used as a dental material for both anterior teeth and posterior teeth.
Claims
1. The yttria content is more than 3 mol% and 5.2 mol% or less, and the maximum frequency of the yttrium concentration distribution shown in the concentration range of 0.5% increments as the Y / Zr ratio in the quantitative element analysis of the energy dispersive X-ray spectroscopy spectrum is 7.5% or less, and the crystal phase is a T phase and a T phase. * A zirconia sintered body, comprising a tetragonal crystal containing a zirconia phase, and having an average crystal grain size of more than 0.41 μm and not more than 1.5 μm.
2. The zirconia sintered body according to claim 1, having a total light transmittance of 43% or more as measured by a method in accordance with JIS K 7361 using a D65 light source.
3. The zirconia sintered body according to claim 1 or 2, which contains alumina.
4. The zirconia sintered body according to claim 3, wherein the alumina content is greater than 0% by weight and not more than 0.1% by weight.
5. The zirconia sintered body according to any one of claims 1 to 4, having a three-point bending strength of 810 MPa or more.
6. A zirconia calcined body having an yttria content of more than 3 mol% and not more than 5.2 mol% for obtaining the zirconia sintered body according to any one of claims 1 to 5.
Citation Information
Patent Citations
Sintered zirconia having high strength and process for production thereof
JP2008050247A
Light-transmitting zirconia sintered compact, method for producing the same and use thereof
JP2010150063A
Sintered body of zirconia and method for manufacturing the same
JP2011073907A
Light-transmitting zirconia sintered compact, zirconia powder and application thereof
JP2015143178A
Zirconia raw material powder and zirconia sintered body
JP2016108176A